A direct monitoring approach for the fatigue safety verification of construction joint details in an existing post-tensioned concrete box-girder bridge. (1st April 2015) - Treacy, Mark A.; Brühwiler, Eugen
Highlights: A novel approach for the safety verification of post-tensioned box girder bridges. Seasonal temperature variation significantly affects crack openings at construction joints. At least one year of measurements is necessary to capture seasonal thermal and traffic variation. This monitoring alleviated the need for expensive strengthening measures on the studied bridge. Abstract: To date, there have been few reports of fatigue problems in medium-span reinforced or prestressed concrete road bridges, primarily due to the high ratio of the dead load to live load in such structures. Where fatigue problems have arisen, they have generally been due to poor detailing issues, sometimes combined with durability problems. One such example is the construction joints of certain post-tensioned concrete road bridges built in Europe during the 1960s and 1970s, which have been found to be fatigue vulnerable. This paper outlines a new approach to the fatigue safety verification of such details incorporating a direct monitoring approach. The study examines the remaining life of construction joint details in a real case study in Switzerland where detailed modelling combined with traditional fatigue load models were found to be insufficient in explaining the real structural behaviour. A long-term monitoring study was performed over three years to accurately determine the real action effects in the reinforcement elements due to thermal and traffic effects and this information is subsequently injected into fatigue damage calculation models. The seasonality of fatigue damage is assessed and the influence of the monitoring duration is examined.